2003
DOI: 10.1152/ajplung.00106.2002
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase C modulates pulmonary endothelial permeability: a paradigm for acute lung injury

Abstract: The intracellular serine/threonine kinase protein kinase C (PKC) has an important role in the genesis of pulmonary edema. This review discusses the PKC-mediated mechanisms that participate in the pulmonary endothelial response to agents involved in lung injury characteristic of the respiratory distress syndrome. Thus the paradigms of PKC-induced lung injury are discussed within the context of pulmonary transvascular fluid exchange. We focus on the signal transduction pathways that are modulated by PKC and thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
68
1
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(70 citation statements)
references
References 189 publications
(273 reference statements)
0
68
1
1
Order By: Relevance
“…The protein kinase C (PKC) family consists of isoforms with different Ca 2ϩ and phorbol ester requirements for activation: conventional (␣, ␤, ␦), novel (⑀, ␥), and atypical (, ) (85,128). PKC␣ has a crucial role in mediating IEJ disassembly either by phosphorylating IEJ components or through inducing the RhoA pathway (76,78,96).…”
Section: Endothelial Scaffoldsmentioning
confidence: 99%
“…The protein kinase C (PKC) family consists of isoforms with different Ca 2ϩ and phorbol ester requirements for activation: conventional (␣, ␤, ␦), novel (⑀, ␥), and atypical (, ) (85,128). PKC␣ has a crucial role in mediating IEJ disassembly either by phosphorylating IEJ components or through inducing the RhoA pathway (76,78,96).…”
Section: Endothelial Scaffoldsmentioning
confidence: 99%
“…Translocation to plasma membrane and phosphorylation of PKC␣ and in vitro phosphorylation of target proteins by PKC␣ have been used as indices of PKC␣ activation (15,35). We previously showed that GDI-1, an inhibitor of Rho-GTPases, is a PKC␣ substrate (4).…”
Section: Activation Of G␣ Q -Plc Pathwaymentioning
confidence: 99%
“…Responses of endothelial cells (ECs) 3 to TNF-␣ and IL-1␤ include up-regulation of adhesion molecules such as ICAM-1, cytoskeletal changes, and permeability increases (1). Mice genetically deficient in receptors for TNF-␣ and IL-1␤ have reduced neutrophil emigration and edema formation in Escherichia coli pneumonia, establishing an indispensable role for these two cytokines in response to this stimulus (2).…”
mentioning
confidence: 99%
“…TNF-␣ induces an increase in permeability in vivo, in the isolated lungs, and in pulmonary microvascular ECs in vitro (1). TNF-␣ also induces cytoskeletal changes within ECs, and the stabilization of F-actin using phalloidin prevents TNF-␣-induced decreases in endothelial barrier functions (3).…”
mentioning
confidence: 99%